Analisis Proses Pengawasan Dalam Pengelolaan Dana Desa Untuk Pembangunan Infrastruktur Desa Pacar Kecamatan Tirto Kabupaten Pekalongan Tahun 2018 (Studi pada Desa Pacar Kecamatan Tirto Kab Pekalongan) - w, hendika dwinanda; -, Kushandajani - (Journal of Politic and Government Studies, 2020)
Abstract: Analysis of the Supervision Process in Managing Village Funds for Infrastructure Development in Pacar Village, Tirto District, Pekalongan Regency in 2018. The process of overseeing village fund management carried out by the community has not proceeded properly. Of the three important aspects of supervision, namely:decision making on the use of village funds, implementation of the use of village funds and supervision of village funds. There are two aspects that are still running properly. The decision making stage for the use of village funds has not been carried out properly, especially in the Aspect of Conformity in the Compilation of Village Fund Planning Procedures because the village head did not make a decree on the Village Fund Implementing Technical Officer (PTPD) but only made a direct appointment to the village secretary and the head of Financial affairs, and the stage of the use of village funds namely in the aspects of the implementation of deliberations and the implementation of village development field activities. the implementation of village deliberations and village development which often coincides with work time are the main reasons for community exclusion. At the stage of supervision everything is proceeding properly, SPJ and LPJ reports on each activity and use of village funds have been made by the village government each time village funds are used. SPJ and LPJ reports become evidence that the use of village funds is not used for personal gain so that the misuse of village funds can be minimized